Enhancing agronomic crop performance: a review of the role of Nano-Diammonium Phosphate (Nano-DAP) in improving soil nutrient status and crop productivity - Nitish Karn; Atin Kumar; Mohsin Ikram; Sharad Sachan; Jitendra Singh; Sunil Kumar; Shubham Shubham; Mohamed A. E. AbdelRahman (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2025)
Nano-diammonium phosphate (Nano-DAP) is a promising source of nitrogen (N) and phosphorus (P₂O₅) for crops and provides an effective remedy for nutrient deficiencies in standing plants. This review highlights the critical role of phosphorus in plant growth and examines the limitations of conventional fertilizers such as urea, DAP, and compost, which, although essential for crop production, often suffer from low nutrient use efficiency and contribute to environmental pollution. Drawing on a synthesis of published studies, this review demonstrates that Nano-DAP enhances phosphorus solubility and availability in soil–plant systems, thereby improving nutrient absorption, stimulating plant growth, and increasing crop yields compared to conventional fertilizers. The review also evaluates the impact of Nano-DAP on yield performance, nutrient uptake, and its application in major field crops. Furthermore, the advantages and potential limitations of Nano-DAP are discussed in the context of sustainable agriculture. Overall, the use of nano-fertilizers, particularly Nano-DAP, presents a promising strategy to improve agricultural productivity while reducing environmental risks.